Production of a female-specific great call in an immature male gibbon, the Nomascus genus - Hradec, Michal; Bolechová, Petra; Svobodová, Ivona (Primates, 2016)
Production of species- and sex-specific vocalisation is a trait characteristic of all gibbons. However, the mechanisms of gibbon vocalisation ontogeny and the manner of developing sex-specific vocal patterns are not yet known. We recorded vocal behaviour of a juvenile male northern white-cheeked gibbon (Nomascus leucogenys). The male produced female-specific great calls. Out of 163 great-call sequences recorded during six sessions, the juvenile son joined in 157 cases with its own great call. In addition, we observed that the juvenile male improved the structure of great calls during the study by including the twitter part. Our results indicate an interesting pattern of vocal ontogeny in Nomascus and suggest a certain degree of plasticity in the vocal signalling in gibbons.
Keywords: vokalizace zvířat; Česká republika; Czech Republic; Vocalization, Animal; Animals, Zoo; Male; Animals; zvířata v ZOO; mužské pohlaví; zvířata; Hylobates